Public Sector Organizational Culture Innovation: Improving General Literacy skills in SD/MI, SMP/MTs in Pesisir Selatan Regency - Aithan, Ibnu; Frinaldi, Aldri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The enactment of law number 23 of 2014 concerning local government and government regulation number 38 of 2017 concerning regional innovation and supported by regent regulation number 7 of 2022 concerning the policy of developing a decent district in order to encourage the creation of an innovative organizational culture in the education sector of the southern coastal district. The research method used in writing this article is descriptive qualitative, the results obtained from this research are in the form of annual school report card data starting from the SD / MI, SMP / MTs levels in the southern coastal district, and which are challenges in improving general literacy in the southern coastal district school environment such as limited infrastructure, availability of books and reading materials, and community mindset. The conclusion is that improving general literacy in the southern coastal district requires a comprehensive and sustainable innovation in public sector organizational culture.